Synthesis and Characterization of Temperature/pH Double-Sensitive Hydroxypropylcellulose/Sodium Alginate Hydrogel (Journal of Fiber Bioengineering and Informatics, 2009)
A series of novel type temperature and pH responsive hydrogels were synthesized by using hydroxypropylcellulose (HPC) as temperature sensitivity material and sodium alginate (SA) as pH sensitivity material. The effect of SA on lower critical solution temperature (LCST) has been studied and the influence mechanism is presented. In addition, the swelling ratio and control factors of swelling process are all researched in this paper. The main results obtained are as follows: the LCST of HPC/SA hydrogel decreased gradually as SA was added into HPC; this kind of hydrogel responded temperature and pH being double-sensitive; the swelling ratio reached the maximum value at pH of 6.
Keywords: HPC; SA; hydrogel; LCST